Mathematical Models for Acoustic Spectra Simulation - Peter Hockicko; Peter Bury; Peter Sidor; Stanislav Jurecka; Igor Jamnicky (Communications - Scientific letters of the University of Zilina, 2010)
The experimentally obtained acoustic spectra of some investigated materials; particularly the ion conductive glasses and MOS (metal–oxide–semiconductor) structures are analyzed using suitable theoretical models and mathematical procedure to fit the experimental data. The acoustic spectra of ion conductive glasses can reflect the basic features of the relaxation and transport processes of the mobile ions. The results obtained form acoustic deep level transient spectroscopy (A-DLTS) spectra of MOS structures are used for the characterization of deep centers and determination of some of their physical parameters. Suitable theoretical model and mathematical description of acoustic spectra are necessary to understand both the principle of the ionic hopping motion and relaxation processes connected with the mobility of conductive ions including the role of their composition and the distribution of interface traps.